A renewed territorial cohesion narrative. Reflections on the EU Territorial Agenda. - Medeiros, Eduardo (Steiner, 2019)
This article debates the need for a renewed territorial cohesion narrative for an updated version of the EU Territorial Agenda. It proposes a more simplistic and practical vision for the territorial cohesion concept and the need to transform it into a measurable notion. It also advances alternative policy implementation avenues to achieve territorial cohesion policy goals at the national level.
Keywords: Regionalpolitik; Raumentwicklungspolitik; Raumentwicklung; Kohäsion; Europäische Zusammenarbeit; EU-Politik; Territoriale Kohäsion; Territoriale Kohäsion